2021
DOI: 10.3390/app112110195
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Recovery Process at Yeongildae Beach, South Korea, Using a Video System

Abstract: Once a beach is eroded by storm waves, it is generally recovered under milder wave conditions. To prevent or reduce damage, it is therefore important to understand the characteristics of the site-specific recovery process. Here, we present the results, based on a data set from a video monitoring system and wave measurements, of the recovery process in a pocketed beach located inside a bay where the shoreline retreated harshly (~12 m, on average, of beach width) during Typhoon TAPAH (T1917) in September 2019. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The temporal scale of the recovery process has not been estimated in Bonggil Beach yet. However, a similar observation was made in Yeongildae Beach that is located ~35 km north of Bonggil Beach (Oh et al, 2021), in which it took ~1.5 yrs for the shoreline of the beach to be recovered back to the level before the time of Typhoon Tapah's attack. Considering that Yeongildae Beach is located inside a bay, and thus the damage by Tapah was smaller than that in Bonggil Beach, it is likely that Bonggil Beach was still in the recovery process when Typhoon Mysak and Heishen affiliated the site in 2020, which was also clear from the profile measurement in Figure 5B.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The temporal scale of the recovery process has not been estimated in Bonggil Beach yet. However, a similar observation was made in Yeongildae Beach that is located ~35 km north of Bonggil Beach (Oh et al, 2021), in which it took ~1.5 yrs for the shoreline of the beach to be recovered back to the level before the time of Typhoon Tapah's attack. Considering that Yeongildae Beach is located inside a bay, and thus the damage by Tapah was smaller than that in Bonggil Beach, it is likely that Bonggil Beach was still in the recovery process when Typhoon Mysak and Heishen affiliated the site in 2020, which was also clear from the profile measurement in Figure 5B.…”
Section: Discussionsupporting
confidence: 55%
“…For example, the data measured by a video monitoring system confirmed that the shorelines in another beach in the eastern coast of the Korean Peninsula (i.e. the beach with similar wave conditions with Bonggil Beach) significantly changed when the storm waves with maximum H s lower than 4 m attacked the site (Oh et al, 2021). This unusual phenomenon was likely related with the recovery process.…”
Section: Simulation Of Shoreline Retreat In 2019mentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, it is necessary to develop measures and plans to mitigate the damage by coastal erosion based on proper risk assessment. These assessments and measures should be carefully set up because the impact by coastal erosion is site-specific due to characteristic conditions in a coastal area and sometimes shows locality even within the same area due to the loss of equilibrium by various factors (Oh et al, 2021). Accurate analysis of sediment transport patterns is, therefore, a prerequisite to developing such measures for the site.…”
Section: Introductionmentioning
confidence: 99%